Seeking a Minor Sun: Saints after the Death of God - Sanders, Theresa (Horizons, 1995)
Theology lives in the days of the frost. Postmodern philosophers question the very possbility of God-language. In response, Edith Wyschogrod's Saints and Postmodernism attempts to develop an ethics grounded in lives of saints. Her definition of "saint" as one devoted to the alleviation of pain is problematic; moreover, her definition does not in fact grow out of hagiography. Rather, it reduces saints' lives to didactic tales. Still, Wyschogrod points toward a more adequate description of the saint as one who sees the being of others as constituted by a lack. An emphasis on otherness is developed in the theologies of Mark Taylor and Charles Winquist. Using their insights and Wyschogrod's, I propose that Christianity turn to the "minor sun" of saints' lives to rethink theology in light of the postmodern critique.